2013
DOI: 10.5688/ajpe778165
|View full text |Cite
|
Sign up to set email alerts
|

Student and Faculty Perceptions of Lecture Recording in a Doctor of Pharmacy Curriculum

Abstract: Objective. To describe students' and faculty members' perceptions of the impact of lecture recording in a doctor of pharmacy (PharmD) curriculum. Methods. Second-and third-year pharmacy students and faculty members completed an anonymous survey instrument regarding their perceptions of lecture recording with 2 classroom lecture capture software programs, Camtasia Studio and Wimba Classroom. Results. Most students (82%) responded that Camtasia was very helpful and almost half (49%) responded that Wimba Classroo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 18 publications
1
40
1
Order By: Relevance
“…Price and Almpanis (2015) found both students and lecturers to be very positive about lecture-recording technology and its capacity to enhance student learning, especially in preparation for assessments. However, others (Larkin, 2010;Maynor et al, 2013;O'Callaghan, Neumann, Jones, & Creed, 2015;Phillips et al, 2007) report on differing perceptions by students and lecturers, with students generally in favour of having immediate access to the recordings, and lecturers remaining undecided and concerned that students may watch a recording rather than attend a face-to-face lecture, which might cause their studies to suffer.…”
Section: Lecture-recording: Benefits and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Price and Almpanis (2015) found both students and lecturers to be very positive about lecture-recording technology and its capacity to enhance student learning, especially in preparation for assessments. However, others (Larkin, 2010;Maynor et al, 2013;O'Callaghan, Neumann, Jones, & Creed, 2015;Phillips et al, 2007) report on differing perceptions by students and lecturers, with students generally in favour of having immediate access to the recordings, and lecturers remaining undecided and concerned that students may watch a recording rather than attend a face-to-face lecture, which might cause their studies to suffer.…”
Section: Lecture-recording: Benefits and Challengesmentioning
confidence: 99%
“…Maynor et al (2013) found that only 10% of their sample of 140 students said they used recordings as a substitute for class; however, nearly half of the same sample said that hypothetically they would be more likely to miss a lecture if they knew it was being recorded. Similarly, in the Marchand, Pearson, and Albon (2014) study only 10% of 210 participating students said they were using recordings as a substitute to attending a lecture.…”
Section: Lecture-recording: Benefits and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…One controversial outcome could be absenteeism with the availability of recorded lectures (Figlio, Rush, & Yin, 2010, Maynor, Barrickman, Stamatakis, & Elliott, 2013. Even if the students attended a typical lecture, it is possible that they could be distracted by their mobile devices and social media during class especially when the recorded lectures are available for them to access at a later time (Colak, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The video lecturing techniques are made simpler and are affordable which allows faculty to use the same recorded lectures so that their research agenda could be strengthened. PRL is not to be confused with lecture capture (LC), which is the real-time recording of an LL that students can utilize to revisit lecture for various purposes (Hadgu, Huynh, & Gopalan, 2016, Maynor, Barrickman, Stamatakis, & Elliott, 2013.…”
Section: Introductionmentioning
confidence: 99%